Symposium 6: Networked Learning and digital technology - Jones, Chris (Proceedings of the International Conference on Networked Learning, 2012)
Networked learning has been defined in the Networked Learning conference series as being based on the use of Information and Communication Technology. The term networked learning acknowledges one aspect of this relationship to computing and to networked computing in particular. This paper explores the relationship of networked learning to technology using an alternative characterisation of new technologies, the term digital, and asks what kinds of implications the digital nature of current technologies have for networked learning. The paper explores the idea of technology and suggests that the term can be used in a number of different ways. It suggests that digital technologies are complex technologies that imply a degree of modularity and recursiveness. The paper suggests that in learning technology digital technology is usually met as part of an infrastructure, understood as a sociotechnical system. The paper argues that despite this complexity there are analytically discernable features of digital technologies that can be thought of as affordances. Using two lenses the paper examines current usage of the idea of the digital in terms of digital natives and digital literacy (-ies) and argues that both ideas are inclined towards technologically determinist outlooks. The paper also notes the particular feature of rapid change in relation to digital technologies and how the nature of the evolution of digital technology relates to digital literacy. The paper concludes by suggesting that research into networked learning needs to take the nature of the digital seriously. A more detailed understanding needs to be developed of what kinds of affordances digital technologies make available. These need to take into account the different meanings of technology and encompass the purposes of digital technologies, the ways they are arranged in assemblages and the way they present themselves as an entire collection of devices in a culture. If insufficient attention is paid to the digital bedrock of technologies then determinist readings of the effects of technology that are based on accounts that are uncritical and lacking in any detailed understanding of digital technologies will prevail.